2022
DOI: 10.3389/fpubh.2022.1027002
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of stigma reduction interventions in Iran: A qualitative study from the perspective of mental health stakeholders

Abstract: IntroductionThe fear and embarrassment associated with stigmas discourage patients from help seeking behavior, which may explain why even the patients' loved ones advise them to discontinue treatment to avoid being labeled. In addition, stigmas can lead to personal and family issues, causing patients to disregard their illness. As such, their disease may develop into a chronic condition. This being said, the present study aims to investigate the challenges, solutions, and successes associated with stigmatizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The mean and standard deviation for GAD-7 were 9.38 and 6. 41 The most important barrier to help-seeking from mental health professionals in the mental disorders population was fear of stigma about mental disorders (M = 2.70, SD = 1.19). In other words, the majority of the participants agreed of strongly agreed (56.5%) with the fear of stigma about mental disorders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean and standard deviation for GAD-7 were 9.38 and 6. 41 The most important barrier to help-seeking from mental health professionals in the mental disorders population was fear of stigma about mental disorders (M = 2.70, SD = 1.19). In other words, the majority of the participants agreed of strongly agreed (56.5%) with the fear of stigma about mental disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the existence of multiple interventions used to reduce the stigma (39-40), these interventions could be effective in reduction of stigma of Iranian mental disorders. As the result of a study in Iran showed, the proposed solutions by mental health stakeholders were mostly raising awareness and training (41).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the-less positive-attitudes of medical students of the first years may reflect those formed during the secondary education or in public life, further research on minors and general population could bring about useful results. Based on them, an appropriate introduction and familiarization with mental illness in the mandatory education could be adopted, and targeted social campaigns (that make good use of media participation and arts as well) could be effectively organized (82)(83)(84).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of self-stigma decreases the willingness of HCWs and their need to seek psychological help. Therefore, stigma reduction programs (e.g., to offer training that will cause the current stereotypes to change) ( 58 ) targeted at HCWs should be organized to encourage positive help-seeking attitudes and intentions, and increase the possibility for these workers to receive mental health treatment.…”
Section: Discussionmentioning
confidence: 99%